The Effectiveness of Digital Application-Based Public Services (NTB Care and Lapor) at the Department of Communication, Informatics, and Statistics of the Province of West Nusa Tenggara - Sulfardin, Sulfardin; Widayat, Rossi Maunofa; Dermawan, M Ariy (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The development of information technology has prompted the government to improve the quality of public services through the use of digital systems. The Provincial Government of West Nusa Tenggara (NTB) developed the NTB Care application and integrated it with SP4N–LAPOR as a platform for managing public aspirations and complaints transparently. This study aims to assess the effectiveness of public services based on the NTB Care and LAPOR applications at the Department of Communication, Informatics, and Statistics of NTB Province, using the policy implementation theory by Van Meter and Van Horn. The research method employed is qualitative descriptive through interviews, observations, and documentation. The results show that the implementation of NTB Care and LAPOR applications has been effective in improving service accessibility, accelerating the follow-up process of complaints, and enhancing transparency and public participation. However, challenges were still found in terms of the equity of network infrastructure, digital literacy of the public, and the limited capacity of service management personnel. This study aligns with the findings of six previous studies regarding the importance of regulatory support, human resources readiness, and technological infrastructure in supporting the success of digital services.